(3QMdI GdYHOQis - (3eMeO Hf eMeO , CHh YHO Gddg GdMGMj Ch (B((3GdMjMj(B) (3GdYHOQj ,fMh (B700 (3g` s ((3GdMSf Hf Ydi Hf CMeO Hf eMeO GdeScGi s)
(3ChdgG (B:s
(3hHYO aEfi bGUO HYO GSJNGQg Gddg SHMGfg Edi JbjjO eG Gecf JbjjOg s
(3BNQgG (B:s
(3abGd bd YgOfG Edjc GfJgJ GdQMdI GdeHGQcI s
(3HgG fXGe GdJYbjHIs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B32 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B244s
Keywords: (3GdLZQGajG h GdHdOGfs